The Implementation Of The Notary Careful Principle In Implementing The Position As A Public Official - Uyunun Nafisa; Setyawati Setyawati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study are: 1) To Know and Analyze the Application of the Principle of Notary Precautions in Carrying Out His Position As a Public Official. 2) To find out and analyze the legal consequences of an authentic notarial deed that does not apply the precautionary principle in carrying out his position as a public official. This research uses the Sociological Juridical Approach Method. The data used in this study are primary, secondary and tertiary data which can support the assessment, which are then analyzed using the Descriptive Analysis and Qualitative Analysis methods. Based on the results of data analysis, it can be concluded that: 1) Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 9 Of 2017 Regarding the Application of the Principle of Recognizing Service Users for Notaries, requires the Notary to be careful in recognizing Service Users and must submit suspicious Transaction Reports to the Reporting Center Financial Transaction Analysis (PPATK) to avoid Notaries as a Means in Money Laundering Activities and provide legal protection to Notaries. 2) The position of an authentic deed which is proven later as money laundering is the responsibility of the tappers because in the Material Aspect (materiele bewijskracht) The information set forth in the official deed (official report) submitted before the Notary (party deed) must be assessed correctly.